Deelemanian ant mimicry: on the natural history and new records of Tapixaua callida Bonaldo, 2000 (Araneae, Corinnidae, Corinninae) - Xavier, Cláudia; Silva-Júnior, Claudio J.; Favacho, César; García, Fabián; Martínez, Leonel; Bustamante, Abel A.; Bonaldo, Alexandre Bragio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
The genus Tapixaua Bonaldo, 2000 is known only by a single species, Tapixaua callida described by Bonaldo in 2000 from Brazil and Peru. The species can be easily recognized by having abundant modified hairs on the apex of the femora, patellae, and tibiae of leg I, a condition previously suggested as instrumental in simulating the cephalic tagma of ants. Herein, we expanded the knowledge on the geographical distribution of the taxon from Huánuco (Peru), and Amazonas and Mato Grosso (Brazil), to Loreto (Peru) and Caquetá (Colombia), to the north, and to the states of Pará and Maranhão, Brazil, to the east, and provided a distribution map with all the records of T. callida obtained so far. Additionally, data on its natural history based on observations, photographs, and videos are presented. The ant-mimiking solution presented by this species, by combining morphological and behavioral elements to trigger resemblance with ants ‘as needed,’ was previously reported only for the South Asian Pranburia mahannopi Deeleman-Reinhold, 1993 and is here named Deelemanian mimicry.